KEPUTUSAN INVESTASI KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Kasus Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia) - Syuria Darma Putra; Nur Hidayati; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTCompany Value is the price that potential buyers are willing to pay when thecompany is sold. Therefore every company will strive to maximize the value of thecompany by having a high company stock price. Investment Decisions, FundingDecisions and Dividend Policy are used as independent variables that areexpected to affect the value of the firm as a dependent variable. This type ofresearch is classified as a quantitative research. The population in this researchis LQ45 Company Registered in Indonesian Stock Exchange (IDX) in 2013 until2017. The method of selecting sampling with purposive sampling method so as toget the number of samples of 28 companies and the number of observations(observation) as many as 140 times. The data used in this research is secondarydata obtained from www.idx.co.id. Data collection techniques with documentationtechniques, in this case the data in question in the form of annual corporatereport. Research data were analyzed by multiple linear analysis. The results ofthis study indicate that investment decisions affect the value of the company whilethe Decree of Funding and the Policy of Dividend has no effect on the value of thecompany.Keywords: Corporate Value, Investment Decision, Funding Decision, DividendPolicy, LQ45 Company, Indonesia Stock Exchange.